Inner Child Dalam Tubuh Dewasa Sebagai Ide Penciptaan Seni Grafis Teknik Relief Print - Rahmadeni Rahmadeni; Yofita Sandra (Journal on Education, 2024)
linoleum cut. The method used is the first, the preparatory phase of observing and collecting information Second, the elaboration phase is the deepening phase by delineating all the data Third, the synthetic phase with matching themes. Fourth, the stage of realization by copying the sketch into a cliché, preparing the tool, and the process of crafting. Fifth, the completion stage is the repair of the work. The result of the work is entitled: (1) Embrace the Glamour of the Wound (2) Shadow of Suspicion (3) Pieces of the Queen of the Doll (4) Clowns of Suffering (5) Emotional Bottles (6) Marrionette Dances (7) Ladies or Gentlemen Reflections (8) Shadows of Trust Issue (9) Key to Mercy (10) Melancholia of Love.